Cloning and Expression of Helicobacter Pylori CagA Gene Antigenic Regions in E. coli - Mahdye Maleki; Mohammad Reza Nassiri; Mojtaba Tahmoores pour3; Kiyarash Qazvini (Fasa University of Medical Sciences, 2016)
Background & Objective: Helicobacter pylori, which has infected about 50 percent of the world population, is one of the most common gastrointestinal pathogens and the most prevalent cause of gastro-intestinal diseases, such as chronic gastric ulcers, gastric and duodenal ulcers, gastric cancer and lymphoma. The CagA Gene (cytotoxin-associated gene A) is a major virulence factor of this pathogenic bacterium. The aim of this study was to construct a recombinant vector carrying the antigenic regions of CagA gene and also to express this gene. Material & methods: The major epitopes of the CagA gene were identified based on bioinformatics. Through this procedure, a gene fragment of 996 bp was isolated by PCR, inserted into a pET32a vector using the enzymatic digestion and then transformed into the E. coli strain BL2I (DE3). Results: The results of sequencing represented the successful cloning of the CagA gene in the expression vector and introducing the accessibility to the antigen. The molecular weight of the produced recombinant protein was estimated 57 KD on an SDS-PAGE gel and the accuracy of the protein expression was verified. Conclusions: The results of this study proved the successful cloning of the epitope area. The recombinant protein can probably be introduced as a good candidate for the production of IgY from the chickenimmunized and the control of Helicobacter pylori infection in humans. It could also be possibly used for the design of diagnostic kits and vaccines for Helicobacter pylori